Era Penyiaran Digital: Pengembangan atau Pemberangusan TV Lokal dan TV Komunitas? - Agung Prabowo (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2012)
Digital TV migration still holds many un-answered questions. Recently, Multiplexing Broadcasting Agencies (LP3M) in seven zones have been defined, while 8 other zones are vacant. The winners of Multiplexing Broadcasting Agencies (LP3M) are actors who currently control televisions in Indonesia. Investment building that will serve emit multiplexing digital signals is key in digital TV business. All broadcasters have to hire to be broadcast. This has caused problems for local and community TV because they have to rent mux (multiplexing) estimated to 40 million per month. Not to mention taht they have to invest equipments for digital-based program. It requires government intervention in term of regulation that protects weak actors from the capital side, such as community TV.